2004
DOI: 10.1074/jbc.m312718200
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Formin, FRLα, Slows Actin Filament Barbed End Elongation, Competes with Capping Protein, Accelerates Polymerization from Monomers, and Severs Filaments

Abstract: Formins are a conserved class of proteins expressed in all eukaryotes, with known roles in generating cellular actin-based structures. The mammalian formin, FRL␣, is enriched in hematopoietic cells and tissues, but its biochemical properties have not been characterized. We show that a construct composed of the C-terminal half of FRL␣ (FRL␣-C) is a dimer and has multiple effects on muscle actin, including tight binding to actin filament sides, partial inhibition of barbed end elongation, inhibition of barbed en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
243
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(258 citation statements)
references
References 29 publications
14
243
1
Order By: Relevance
“…In vitro, the FH2 domain nucleates actin filaments from monomers Sagot et al, 2002b;Kovar et al, 2003;Li and Higgs, 2003;Harris et al, 2004;Kobielak et al, 2004), but distinct from other nucleators, it remains associated with the growing barbed end to promote elongation, even in the presence of barbed-end capping proteins Kovar et al, 2003;Li and Higgs, 2003;Pring et al, 2003;Harris et al, 2004;Kobielak et al, 2004;Moseley et al, 2004). The FH1 region is a proline-rich stretch that recruits profilin, an actin-monomer binding protein essential for formin function in vivo , to participate in FH2-mediated nucleation in vitro (Sagot et al, 2002b;Kovar et al, 2003;Pring et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the FH2 domain nucleates actin filaments from monomers Sagot et al, 2002b;Kovar et al, 2003;Li and Higgs, 2003;Harris et al, 2004;Kobielak et al, 2004), but distinct from other nucleators, it remains associated with the growing barbed end to promote elongation, even in the presence of barbed-end capping proteins Kovar et al, 2003;Li and Higgs, 2003;Pring et al, 2003;Harris et al, 2004;Kobielak et al, 2004;Moseley et al, 2004). The FH1 region is a proline-rich stretch that recruits profilin, an actin-monomer binding protein essential for formin function in vivo , to participate in FH2-mediated nucleation in vitro (Sagot et al, 2002b;Kovar et al, 2003;Pring et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the FH1 domain of formins can mediate interactions with profilin, an abundant actin-binding protein, thereby sequestering actin monomers Sagot et al, 2002b;Moseley et al, 2004). The FH2 domain provides the activity for nucleation of actin cables Sagot et al, 2002a;Kovar et al, 2003;Harris et al, 2004;Moseley et al, 2004). This domain is the most conserved and best characterized domain within formins and was used as a basis for the phylogenetic classification of over a hundred formins (Higgs and Peterson, 2005).…”
Section: The a Gossypii Formin Family Membersmentioning
confidence: 99%
“…The budding yeast formin Bni1p also binds the actin monomer-binding protein Bud6p, which, similar to profilin, stimulates the activity of the FH2 domain (Moseley and Goode, 2005). In addition to their activity in actin filament nucleation and elongation, some formins have been suggested to also function in actin bundling and severing, further contributing to the remodeling of actin structures (Harris et al, 2004Moseley and Goode, 2005;Harris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%